Is the value of urodynamics undermined by poor technique?: ICI‐RS 2018. (10th December 2019) - Gammie, Andrew; Almeida, Fernando; Drake, Marcus; Finazzi Agrò, Enrico; Kirschner‐Hermanns, Ruth; Lemos, Nucelio; Martens, Frank; Mehnert, Ulrich; Rosier, Peter; Valentini, Francoise; Abrams, Paul
Abstract: Introduction: The quality of urodynamic measurements in clinical practice has been debated as a matter of concern. It is considered plausible that this has a direct bearing on patient care and the perceived value of urodynamic testing. Methods: This is a report of the proceedings of the Think Tank: "Is the value of urodynamics undermined by poor technique?" from the Annual International Consultation on Incontinence—Research Society, which took place in June 2018 in Bristol, UK. The Think Tank discussed the evidence for deficiencies in urodynamic test quality and considered the implications of improvements for clinical diagnosis and practice. Results: There is evidence that technique affects urodynamic quality, and that urodynamic practice is variable. Factors such as team skill set, technologies used, and training received will also affect the quality of urodynamic service. Questions exist regarding the influence of technique on the utility and perceived value of urodynamics. Conclusions: We suggest research questions that will provide the necessary evidence on the link between technique, reporting, and outcome, and clarify the role of good practice in the utility of urodynamic testing.